Tingkat Agresivitas Pajak Sebelum dan Pada Saat Pandemi Covid-19 Pada Perusahaan Farmasi di Indonesia dan Malaysia yang Dimoderasi Kinerja Keuangan Perusahaan - Evi Juita Wailan' An; Sonya Enda Natasha S Pandia (Institut Bisnis dan Informatika Kesatuan, 2022)
This study aims to examine and analyze the effect of Inventory Intensity, Capital Intensity, Sales Growth and the Audit Committee on Tax Aggressiveness during the Pandemic in Indonesia and Malaysia and to determine the level of corporate tax aggressiveness that occurred during the Covid-19 pandemic in both countries with an observation period. is from 2019 to 2020. The population in this study is a Manufacturing company in the Consumer Goods Industry sector with a Pharmaceutical Sub-Sector listed on the Indonesia Stock Exchange during the 2019-2020 period which operates 9 companies, and also a Health Care Sector company with a Pharmaceuticals Sub-Sector listed on the Malaysia Stock Exchange during the 2019 period. - 2020 which re-opens 6 companies. The sampling technique used in this study is the saturated sample. Simultaneously, Inventory Intensity, Capital Intensity, Sales Growth, and the Audit Committee have no effect on Tax Aggressiveness both in Indonesia and Malaysia before and during the COVID-19 pandemic, because tax aggressiveness is carried out by the company in accordance with the company's management planning, not because it is based on national economic conditions. Partially, Inventory Intensity, Capital Intensity, Sales Growth, Audit Committee have no effect on Tax Aggressiveness for the companies studied on the Indonesia Stock Exchange, while in Bursa Malaysia Inventory Intensity has no effect on Tax Aggressiveness, for Capital Intensity, Sales Growth, the Audit Committee has no effect on Tax Aggressiveness